2006
DOI: 10.3766/jaaa.17.7.7
|View full text |Cite
|
Sign up to set email alerts
|

Improving Speech Intelligibility in Background Noise with an Adaptive Directional Microphone

Abstract: Omnidirectional, supercardioid, and adaptive directional microphones (ADM) were evaluated in combination with the ADRO amplification scheme for eight participants with moderate sloping hearing losses. The ADM produced better speech perception scores than the other two microphones in all noise conditions. Participants performed the Hearing in Noise Test sentences at -4.5 dB SNR or better, which is similar to the level achievable with normal hearing. The Speech, Spatial and Qualities of Hearing Scale indicated n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 19 publications
2
28
0
Order By: Relevance
“…For example, Ferguson and KewleyPort found that patients with mild SNHL accurately identified 73 percent of vowels at speech-to-babble ratios of -3 dB, i.e., well below typical SeRTs [8]. As a result, improving consonant comprehension is a major focus of current research on hearing aid design [9][10][11] and adaptive perceptual training [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ferguson and KewleyPort found that patients with mild SNHL accurately identified 73 percent of vowels at speech-to-babble ratios of -3 dB, i.e., well below typical SeRTs [8]. As a result, improving consonant comprehension is a major focus of current research on hearing aid design [9][10][11] and adaptive perceptual training [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies (6,7,8) report that these features are important to improve understanding in noisy environments, the evidences found do not clarify whether the elderly can benefit from these settings.…”
Section: Introductionmentioning
confidence: 97%
“…In order to improve speech intelligibility, and hence, the performance of its members, hearing aids noise reduction algorithms and different types of microphones have been developed and incorporated to hearing aids, which have the purpose to reduce the signal/noise in the environment (4,5) . The noise reduction algorithms are meant to attenuate the intensity of noise, when it exceeds a certain proportion in relation to the speech signal (6,7) , which may promote speech intelligibility, reduce the discomfort to the sounds and the effort to listen.…”
Section: Introductionmentioning
confidence: 99%
“…Directional microphones are more sensitive to sounds coming from a certain direction, generally from the front of the head, reducing sounds that come from other directions (8,9) . The improvement in the signal/noise ratio (S/N) in directional microphones varies by 3-5 dB, contributing to the intelligibility of the speech signal (10) .…”
Section: Introductionmentioning
confidence: 99%